DAMPAK PERATURAN PESANTREN BAGI KEDISIPLINAN SANTRI PONDOK PESANTREN AL HAMIDIYAH BAHRUL ULUM TAMBAKBERAS JOMBANG - Muhammad Syukron Naim; Hilyah Ashoumi (JoEMS (Journal of Education and Management Studies), 2020)
Islamic Boarding School Regulations are policies formulated by Islamic Boarding Schools so that education runs systematically so as to achieve the desired goals. And Discipline is an attitude of respecting and respecting a regulation that applies both written and unwritten. However, there are still rules that have not yet been carried out affective, marked by Santri junior high school students who smoke, leave without permission, carry mobile phones, and deal with the opposite sex who violate syara '. This study aims to determine the state of Al-Hamidiyah Islamic Boarding School regulations and find out whether or not the impact of Islamic boarding school regulations on the discipline of students and their level of presentation. In writing this thesis the author uses quantitative methods. The sampling method used by the authors in this study is simple random sampling, ie taking sample members from a population taken at random. The sample in this study were 100 students at Al-Hamidiyah Islamic Boarding School. Data were analyzed with validity, reliability, and simple regression tests (t test) using the SPSS 22.0application for windows. The results showed that the application of the existing regulations at Al-Hamidiyah Islamic Boarding School was classified as good with a percentage of 49%. And Pesantren regulations have a significant impact on the discipline of the Al-Hamidiyah Islamic Boarding School Santri. The percentage rate is 10%.